Building an action plan to tackle palliative care inequality through multi-stakeholder platforms - Miguel Antonio Sánchez-Cárdenas; Marta Ximena León-Delgado; Luisa Fernanda Rodríguez-Campos; Juan Esteban Correa-Morales; Laura Vannesa González-Salazar; Ángela María Cañón Piñeros; Genny Paola Fuentes-Bermúdez; Lina María Vargas-Escobar (Palliative Care and Social Practice, 2023)
Background: To achieve universal care and overcome existing barriers, the most effective strategy is to devise an action plan that incorporates palliative care into primary health care (PHC), as recommended by the World Health Organization’s (WHO) Astana Declaration. In Colombia, a country with an upper-middle-income status, about 128,000 individuals experience severe health-related suffering (SHS) that necessitates palliative care. Although the country’s healthcare system has made steady strides in the integration and development of palliative care, there is still no national plan in place for palliative care. Objective: Build up Colombia’s palliative care plan through stakeholder consensus. Method: Based on the participatory action research method and the multi-stakeholder platforms model, this study convened 142 stakeholders from different levels of the health system (patient representatives, journalists, health professionals, government entities, insurance companies, universities, and drug regulatory authorities) Results: The national plan aims to achieve its objectives through a series of strategic actions. These include integrating and diversifying palliative care services, improving access to opioids, increasing palliative care education, promoting community-based palliative care programs, securing funding, and implementing a regulatory framework for palliative care by public policymakers. Conclusions: The national palliative care is an alliance that aims to reduce palliative care inequity in Colombia by 2026 by empowering stakeholders nationwide to collaborate around specific goals and objectives.